Providing Palliative Care for Patients Affected by Coronavirus Disease 2019: Insights on Ethical Difficulties in Honoring and Fulfilling Patients’ Requests - John Weru (Palliative Medicine and Hospice Care, 2024)
The World Health Organization (WHO) defines palliative care as: “an approach that improves the quality of life of patients and their families facing the problem associated with life-threatening illness, through the prevention and relief of suffering by means of early identification and impeccable assessment and treatment of pain and other problems, physical, psychosocial and spiritual.”